(untitled) (Physical Education, Health and Social Sciences, 2026)
Chromium metal pollution is extremely harmful to plant growth as well as environmentally sustainable conditions. Therefore, an experiment was designed to investigate the impact of chromium stress on morphological, physiological, and biochemical parameters of chickpeas (Cicer arietinum L.). Chromium treatment at a dose of 20 mg kg⁻¹ was given through soil medium to investigate the effects. Ten chickpea cultivars including parents along with mutant genotypes were utilized in the experiment which was conducted in CRD technique. It was found that growth attributes, namely shoot length, root length, and biomass, were greatly affected by chromium-induced stress in both parents and mutants. Chlorophyll pigments, including chlorophyll a, chlorophyll b, and total chlorophyll, were highly suppressed in the presence of chromium. On the other hand, oxidative stress parameters such as the content of reactive oxygen species, malondialdehyde, hydrogen peroxide, and antioxidant enzymes, including CAT, POD, and APX, were highly elevated. Moreover, osmoprotectants and secondary metabolites like proline, total soluble sugars, phenols, and flavonoids showed variation between different cultivars, suggesting different tolerance strategies. There were statistically significant variations between different treatments and cultivars, where the chromium stress had highly significant impacts on most of the investigated characters at 5 percent probability level. In summary, the results indicate that chromium toxicity is associated with generation of oxidative stress in plants and inhibits their growth, and that the improved antioxidant defense system plays a key role in conferring stress resistance to some chickpea varieties.